Teknik Terapi Seni Islami dan Presfektif Konseling Islam - Ahmad Wajahtera; Nurjannah Nurjannah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This research is a literature study that discusses Islamic art therapy and its application. Islamic Art Therapy is one form of therapy that has not been widely used today. Islamic Art Therapy is a form of therapy that involves an artistic process, such as drawing a symbolic form of a therapeutic relationship to help the therapist gain an understanding of oneself and the stresses experienced by the client. Islamic Art Therapy has the characteristics of non-verbal communication, metaphor as a means of therapy, and relationship orientation. Islamic Art Therapy has not been widely applied to the problems of clients with psychological disorders.